Nano‐Memristors with 4 mV Switching Voltage Based on Surface‐Modified Copper Nanoparticles. Issue 20 (11th April 2022) - Liu, Peisong; Hui, Fei; Aguirre, Fernando; Saiz, Fernan; Tian, Lulu; Han, Tingting; Zhang, Zhijun; Miranda, Enrique; Lanza, Mario
Abstract: The development of memristors operating at low switching voltages <50 mV can be very useful to avoid signal amplification in many types of circuits, such as those used in bioelectronic applications to interact with neurons and nerves. Here, it is reported that 400 nm‐thick films made of dalkyl‐dithiophosphoric (DDP) modified copper nanoparticles (CuNPs) exhibit volatile threshold‐type resistive switching (RS) at ultralow switching voltage of ≈4 mV. The RS is observed in small nanocells with a lateral size of <50 nm –2, during hundreds of cycles, and with an ultralow variability. Atomistic calculations reveal that the switching mechanism is related to the modification of the Schottky barriers and insulator‐to‐metal transition when ionic movement is induced via external bias. The devices are also used to model integrate‐and‐fire neurons for spiking neural networks and it is concluded that circuits employing DDP‐CuNPs consume around ten times less power than similar neurons implemented with a memristor that switches at 40 mV. Abstract : The development of memristors operating at low switching voltages can be very useful to avoid signal amplification in many types of circuits. Here, 400 nm‐thick dalkyl‐dithiophosphoric modified copper nanoparticles (DDP‐CuNPs) based nano‐memristors (<50 nm 2 ) exhibiting volatile threshold‐type resistive switching at an ultralow switching voltage of ≈4 mV, and with an ultralow variability, are reported.